Neue Universitätsrankings für die Schweiz: Geist und Geld - Benjamin Krebs; Joel O'Neill (Center for Research in Economics, Management and the Arts (CREMA), 2014)
University rankings are often used as indicators for university quality by scholars and policy makers. The main indicators common to all well-established rankings are the number of publications in well-known journals, and the citation frequency of these publications. In this paper we take a closer look at such rankings. We state, that they suffer from three major deficiencies: first, none of the main indicators relate input (i.e. funding) to output; second, no university ranking provides information about the marginal productivity of universities and third, the established rankings may bias the focus of academics and university leaders onto rank instead of actual university quality. In contrast to the third deficiency, the first and second have received scarce attention. Thus, we adjust two of the most recognized rankings for Swiss universities by relating research output to the respective university budget. Our adjusted rankings show quite a different picture: While larger universities lead the unadjusted rankings, they find themselves at the bottom of the adjusted rankings, i.e. the original rankings are almost completely inverted. Our results show, that the first deficiency of standard rankings is severe but can be cured easily. This also has important consequences for the second deficiency about which we can, however, only speculate.
Keywords: 330